ANALISIS RISIKO KEAMANAN SIBER DAN STRATEGI PERLINDUNGAN DATA PADA E-COMMERCE UMKM DI INDONESIA - Setiadi, Teguh (Journal of Computer Science and Technology (JCS-TECH), 2026)
The rise of e-commerce has created significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to access a broader market. However, this digital age also brings considerable cybersecurity risks, including data leaks and cyberattacks. This study investigates cybersecurity risks in MSME e-commerce in Indonesia, evaluates their impact on consumer trust, and proposes practical solutions. Using a mixed-method approach that includes a literature review, interviews with MSME stakeholders, and case study analysis, this research identifies key challenges such as inadequate cybersecurity awareness and limited technological infrastructure. Findings indicate that implementing encryption technology, conducting cybersecurity training, and fostering partnerships with technology service providers can significantly enhance MSME data protection. The study contributes to both academic research and policy development in the field of cybersecurity for MSMEs.